The effect of different working fluids and internal geometries on the efficiency of evacuated tube heat pipe solar collectors - Mukuna, Jean Gad; Gryzagoridis, Jasson (Journal of Energy in Southern Africa, 2020)
In this study, a heat pipe was modified with designed and manufactured inserts of specific profiles in order to investigate the effect of the internal geometries and working fluids on the efficiency of the evacuated tube heat pipe solar collector. The experimental rig was made of a mobile frame, an insulated water tank, a solar simulator and an evacuated tube heat pipe. Using an average irradiance of 700 watts per square meter, the indoor tests were conducted first on a heat pipe without any working fluid (dry mode) and later on the heat pipe containing, in turn, each of the six working fluids for each of the five geometries. Results show that, when inserting different profiles in the heat pipe, there is an enhancement of the heat transfer and hence an increase in the efficiency of the evacuated heat pipe solar collector.